The Trial on the Effectiveness of Honey on White Rats Using Geliate Acetate Method An Experimental Study in Male Wistar Rat - Goenarwo, Edijanti; Chodidjah, Chodidjah; Susanto, Heri (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: Pain is the most common complaint of a disease that can be reduced using the analgesic drugs. Besides the pharmacological medication, the traditional medications are available including honey containing flavanoid. The compound can protect the lipid membrane from the damage and inhibit cyclooxygenase, the main path of the synthesis mediator for pain like prostaglandin. This study aims at finding out the efficacy of analgesic of honey using geliate asetate method.Design and methods: In an experimental study using post test only control group design, 25 Wistar rat (80-90 days, BW 180-220 gr) were randomly divided into 3 groups of 5 mice each. Gp1: =aquadest (negative control), Gp2: 0.675 g/BW honey, Gp3: 1.35g honey Gr 4: 2.7 g/kgBW honey and Gr 5 (possitive control): 4.5 mg/ BW of paracetamol. 5 minutes after the treatment, an intraperitoneal injection of acetic acid was given for all groups. Anova followed by post Hoc test was used for data analysis.Result: The honey concentration of 50% (1.35) g was found to have increasing effect of analgesic while the concentration of 25% and 100 % showed a reducing analgesic effect.Conclusion: Honey has been shown to have an analgesic effect in mice with the effective concentration of 50% (1.35 g/kgBW) (Sains Medika, 3(1):48-53).